Statistical estimation of modern demographic losses in Ukraine - Palian Z. О. (Statistics of Ukraine, 2016)
The population of Ukraine, like in the similar to most countries of Europe, is living within the narrowed regime of replacement, which leads to depopulation. This process is conditioned not only by objective demographic factors. On the different historical stages depopulation in Ukraine was accelerated through negative influence of economic crisis and social catastrophes. During the 20th century the Ukrainian population suffered considerable tragic losses as a result of artificial famine in 1921-1923, 1932-1933, 1946-1947, World War II and post-war repressions. During the 2002-2013 has been intensified the process of demographic potential recovery, increase of fertility and life expectancy, reduced the excess of males mortality, especially in active reproductive and working age. But in 2014 as a result of military conflict between Russia and Ukraine, occupation of the territory of Republics of Crimea and part of Eastern Ukraine, the population had experienced considerable losses. In this work we attempt to estimate the demographic consequences of annexation of Crimea, in particular, size of the real and expected demographic losses in Ukraine in a short-term prospect. For this purpose, the statistical methods of modeling and projections, and also cohort-component method had been used. This study uses the data of the State Statistics Service, Ministry of Social Policy of Ukraine and some official data of the Federal State Statistics Service of the Republic of Crimea. As a result of annexation and taking into account the overall negative population growth, Ukraine has lost 2 486 thousand people, including only by temporary occupation of Republic Crimea - 2 342 thousand (1.01.2015). With the evolutionary changes of the population and its reproduction characteristics (as in “peaceful times”), resident population would amount 45.08 million and the age structure of the population is more older (1.01.2015). Due to the exclusion of the population, living in the Crimea and Sevastopol, population of Ukraine is noticeably getting younger: increases the share of young children up to 5 years and adults older than 65 years. Consequently, the level of aging declines by 1% to 14.4%. At the same time, reduced the percentage of children of middle age can affect the prospectively reproductive population contingent. The mentioned structural changes will lead to corresponding changes of the rates of natural increase. A “younger” hypothetical population structure excluding annexed territory will contribute to a slight increase in fertility and a serious decrease of mortality and of the negative natural growth. Abstracting from possible deepening of the military conflict and expanding of the occupied territory, in 2019 the population could decrease to 41.95 million (in the case of non-return of annexed territory of the Crimea and Sevastopol).